Association of ApoE ε 4 allele with blood lipid and prognosis in acute ischemic stroke patients - Ya-jing ZHANG; Zhi-hong SHI; Wei YUE; Shu-ling LIU; Xiao-dan WANG; Meng-yuan LIU; Ya-lin GUAN; Yong JI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To explore the relationship between apolipoprotein E ε4 (ApoEε4) allele and blood lipid, and the relationship between ApoE ε 4 allele and the prognosis of acute ischemic stroke.  Methods The study included 786 patients with acute ischemic stroke admitted in Tianjin Huanhu Hospital from December 1, 2013 to June 30, 2014. The ApoE genotype was determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), ApoA, ApoB levels were also measured. The relationship between ApoE ε 4 allele and blood lipid was analyzed. All patients were assessed by National Institute of Health Stroke Scale (NIHSS) on discharge, and they were divided into 2 groups according to NIHSS score: favorable prognosis group (NIHSS ≤ 10) and unfavorable prognosis group (NIHSS > 10). The relationship between ApoE ε 4 allele and the outcome was analyzed by univariate and forward multivariate Logistic regression analysis.  Results The ApoEε 4 allele carriers had significantly higher LDL-C and ApoB levels than the non-ApoEε4 allele carriers [(3.25 ± 0.85) mmol/L vs (3.00 ± 0.83) mmol/L, P = 0.008; (1.20 ± 0.30) mmol/L vs (1.09 ± 0.25) mmol/L, P = 0.000]. Forward multivariate Logistic regression analysis showed NIHSS score on admission and modified Rankin Scale (mRS) on discharge were the major influencing factors for prognosis of acute ischemic stroke (P = 0.000, for all). The ApoE ε 4 had no significant outstanding influence on the outcome of acute ischemic stroke (P = 0.343).  Conclusions The presence of ApoE ε 4 allele do not predict a worse outcome of acute ischemic stroke, but it is associated with increased LDL-C and ApoB in acute ischemic stroke.   DOI: 10.3969/j.issn.1672-6731.2015.02.007